Indonesia’s Educational Policies on Madrasah Diniyah (MD) - Badrudin Badrudin (Jurnal Pendidikan Islam, 2017)
Since the government has more powers and authorities and bigger sources in enforcing its powers, it seems dominant in producing policies on MD that favor its political interest. This study was aimed at investigating the educational policies on MD before and after the Law No. 4 of 1950 Jo No. 12 of 1954, the educational policies of the MD Act No. 2 Year 1989, and the educational policies of the MD under law No. 20 Year 2003. In addition, it also examined the government's policies on MD in Indonesia from the beginning of independence day (1945) to  (2017). The method used was descriptive qualitative including steps of collecting data, classifying the data, interpreting and presenting the data. This study found that the educational policies on MD were not made by the government to prioritize MD in national education system. The policies on MD education covering before and after the Law of education and teaching No. 4 1950 Jo No. 12 Year 1954, UUSPN No. 2 Year 1989, and UUSPN No. 20 Year 2003, has not supported MD as an integral part in the provision of national education system in Indonesia. They have favored the interests of central government so that they have caused the difficulties in its implementation by the public at the local level.